Surface reactions with participation of oxides of molybdenum and tungsten - A. F. Guseva; M. V. Trifonova (Chimica Techno Acta, 2015)
The kinetics of surface reactions in one-dimensional and radial (two-dimensional) distribution of diffusant MoO3 (WO3) on the surface of the substrate MeO (Me is Cd, Ni, Pb, Mn, Cu) were investigated. A kinetic equation satisfactorily describes the rate of surface reactions in the case of radial distribution of diffusant on the substrate. It’s found that when the radial distribution of diffusant the growth of layer on the substrate surface eventually slows down and stops almost completely, due to the outflow of the diffusant deeps into the substrate. When the one-dimensional distribution of diffusant the surface interaction is not slowed down and does not stop at an arbitrarily large times.